Inhaled corticosteroids and risk of lung cancer: A systematic review and meta‐analysis. (29th October 2020) - Lin, Ping; Fu, Siyu; Li, Weijing; Hu, Yuehong; Liang, Zongan
Abstract: Introduction: Current studies investigating the association between inhaled corticosteroid (ICS) use and risk of lung cancer have yielded inconsistent findings. The aim of this systematic review and meta‐analysis was to pool all currently available data to estimate this association. Methods: We systematically searched MEDLINE (1946 to July 2020), EMBASE (1974 to July 2020) and the Cochrane Library (June 2020) via Ovid to identify relevant articles investigating the association between the ICS use and the risk of lung cancer. Random‐effects analysis was used to calculate pooled relative risks (RRs) with 95% confidence intervals (CIs). Results: Ten articles including 234 920 patients were analysed. ICS use was identified to have a decreased risk of lung cancer in chronic obstructive pulmonary disease (8 studies, 1806 patients; RR = 0.73, 95% CI: 0.61–0.87, P < .01; I 2 = 60.0 %), asthma (1 study, 41 438 patients; RR = 0.44, 95% CI: 0.34–0.57, P < .01) and mixed (1 study, 46 225 patients; RR = 0.79, 95% CI: 0.69–0.90, P < .01) patients. The findings of reduced risk of lung cancer were consistent in all subgroup analyses except for the short‐term follow‐up (≤5 years) (RR = 0.94, 95% CI: 0.81‐1.07, P = .34) and free of immortal time bias (RR = 0.94, 95% CI: 0.82‐1.08, P = .38) subgroups. Conclusions: The present study suggested that ICS use was associated with decreased risk of lung cancer. However, our findings should be interpreted with caution because most original studies were judged to be at high risk of immortal time bias.